Study of the Relationship Between “Attitude Towards Mathematics” and “Attitude Towards Mathematical Problem-Solving” among Students of two Costa Rican Public Day Schools - Chacón Fernández, Ronny (2024)
The main objective of the research was to study the relation between the level of attitude towards mathematics and the attitude towards mathematical problem-solving in the students of two Costa Rican official day schools (whose names are omitted for reasons of confidentiality) enrolled in 2022 by analyzing the existence of differences by sex, by level of study, and by school. The research is of a quantitative, descriptive-exploratory type. The sample consisted of 528 students, and the sampling design was simple random stratification according to school and educational levels. The statistical techniques applied were Student’s t-test and one-factor ANOVA for the study of the research hypotheses. The results indicate that 65.9% of students have a positive attitude towards mathematics and 80.1% have a positive attitude towards mathematical problem-solving, and that there are differences between men and women in both variables, showing the first higher levels with a low effect size but no differences by school. In addition, there were differences between the seventh-grade students with respect to the ninth and tenth-grade students in the variable attitude towards mathematics but not in the attitude towards mathematical problem-solving. Finally, a positive, significant, and direct relationship was found between these variables.